Driving sustainability: assessing KPI effectiveness in the Saudi chemical industry - Alfarsi, Alaa; Sherif, Ziyad; Jagtap, Sandeep; Gupta, Sumit; Salonitis, Konstantinos (Springer, 2024)
This study explores the relationship between Key Performance Indicators (KPIs) and environmental performance improvement within the Saudi chemical industry. Against the backdrop of global sustainability imperatives and Saudi Arabia’s Vision 2030, which promotes sustainability for economic diversification, this research aims to assess the effectiveness of KPIs in driving environmental sustainability practices. The motivation for this study stems from the identified gaps in the systematic implementation and utilisation of KPIs and the lack of awareness regarding certain aspects of environmental impact management within the industry in the Kingdom. The methodology involved a structured survey administered to a diverse range of chemical manufacturing companies, followed by rigorous data analysis using descriptive evaluation, Analysis of Variance (ANOVA), reliability analysis, and t-tests. The results revealed insights into pollution areas, KPI utilisation, methods for pollution assessment, alignment with strategic goals, and governance regulations. Descriptive analysis highlighted air quality management as a priority, with notable attention to water and land pollution, while quantitative analysis confirmed the significance of KPIs in driving environmental performance improvement in the area. However, it also unveiled the absence of a systematic approach to implementing and utilising KPIs effectively, coupled with a lack of awareness regarding certain aspects of environmental impact management, consequently leading to uncertainty. Overall, this study contributes to advancing sustainability efforts within the Saudi chemical sector, providing actionable insights for industry stakeholders and policymakers.
Keywords: Sustainability; Saudi Arabia; Chemical industry; Sustainable practices; Key performance indicators (KPIs); 40 Engineering; 4011 Environmental Engineering